Implementasi Penyelesaian Sengketa Waris Keluarga Beda Agama Dalam Persfektif Hukum Islam - Muhammad Syamsul Huda; Imron Choeri; Syamsul Ma’arif (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
Abstract: The aim of this research is to analyze the implementation of inheritance rights for children of different religions according to Islamic law and to try to resolve the distribution of inheritance rights for children of different religions according to Islamic law. Nowadays, the problem of inheritance between religions has become a modern problem because there is no explanation in the Al-Qur'an or Hadith regarding the distribution of inheritance to heirs of different religions. Standard jurisprudence is used as an approach to this research. The research results show that the Hadith regulates the inheritance rights of children who are not Muslim. However, the Supreme Court of the Republic of Indonesia has determined that heirs who are Muslim have rights over heirs who are not Muslim. The focus of this research is the regulation of inheritance rights for children of different religions according to Islamic law and efforts to resolve the distribution of inheritance rights for children of different religions. As an analytical method, qualitative methods are used, namely